2012
DOI: 10.1542/peds.2011-3548
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Prongs or Mask for Nasal Continuous Positive Airway Pressure in Preterm Infants

Abstract: In premature infants, NCPAP was more effective at preventing intubation and ventilation within 72 hours of starting therapy when given via nasal masks compared with nasal prongs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
89
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 16 publications
8
89
0
1
Order By: Relevance
“…There was no statistically significant difference with p value of 0.080. In study done by Emily A. Kieran et al [7] , the investigators found that thirty-two of the 62 (52%) infants randomly assigned to nasal prong group were intubated and ventilated within 72 hours of starting NCPAP compared with 16/58 (28%) infants randomly assigned to nasal mask group (P=.007). They concluded that CPAP support with nasal mask was better than CPAP support with nasal prong, as within 72 hrs of starting CPAP support less number of patients were intubated and ventilated in nasal mask group, while in our study we did not observe any such difference between nasal mask and nasal prong group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no statistically significant difference with p value of 0.080. In study done by Emily A. Kieran et al [7] , the investigators found that thirty-two of the 62 (52%) infants randomly assigned to nasal prong group were intubated and ventilated within 72 hours of starting NCPAP compared with 16/58 (28%) infants randomly assigned to nasal mask group (P=.007). They concluded that CPAP support with nasal mask was better than CPAP support with nasal prong, as within 72 hrs of starting CPAP support less number of patients were intubated and ventilated in nasal mask group, while in our study we did not observe any such difference between nasal mask and nasal prong group.…”
Section: Discussionmentioning
confidence: 98%
“…Nasal prong and nasal mask has been commonly used for providing nasal CPAP in neonate. Recently this comparison between these two interfaces had been done by Emily A. Kieranet al [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Assessing nasal skin status only at nares may miss the trauma caused by the nasal mask. Previous studies have reported equal incidence of nasal injury with both the interfaces [4,6]. A recent study has reported lower incidence of nasal injury on rotating the use of nasal prong and nasal mask than on isolated use of each interface [7].…”
mentioning
confidence: 95%
“…Search for a better nasal interface has resulted in emergence of nasal mask as an alternative CPAP interface. However, evidence on relative efficacy of nasal prongs and nasal mask is sparse [4]. The randomized controlled trial by Goel, et al [5], published in this issue of Indian Pediatrics, compares nasal mask and nasal prongs for CPAP delivery in neonates born at less than 34 weeks of gestation.…”
mentioning
confidence: 99%
See 1 more Smart Citation